2019
DOI: 10.1029/2019wr024973
|View full text |Cite
|
Sign up to set email alerts
|

Catchment Travel Times From Composite StorAge Selection Functions Representing the Superposition of Streamflow Generation Processes

Abstract: Catchment travel times integrate the multitude of hydrological flow processes and provide insights into catchment functioning. StorAge Selection (SAS) functions describe how residence times of water in storage are related to travel times of water in catchment outflows. As such, SAS functions are useful to summarize transport processes in catchments and are ideal to simulate catchment outflows and the concentrations of various solutes and tracers. Recent studies suggested that using one probability distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 98 publications
(218 reference statements)
4
68
0
1
Order By: Relevance
“…Recent numerical experiments on real or virtual hydrological systems (Danesh‐Yazdi, Klaus, Condon, & Maxwell, 2018; Kaandorp, de Louw, van der Velde, & Broers, 2018; Remondi et al, 2018; Yang, Heidbüchel, Musolff, Reinstorf, & Fleckenstein, 2018) showed that, even if SAS functions simplify the shapes of the age distributions compared with TTDs, they may not be described well by unimodal distributions. Rodriguez and Klaus (2019) used high frequency (i.e., sub‐daily) stable isotopes in precipitation and discharge over 2 years and found that the SAS function in a slate catchment with complex flow paths may contain several peaks consistent with experimentally identified discharge generation processes.…”
Section: Acknowledging the Multimodality Of Water Age Distributionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent numerical experiments on real or virtual hydrological systems (Danesh‐Yazdi, Klaus, Condon, & Maxwell, 2018; Kaandorp, de Louw, van der Velde, & Broers, 2018; Remondi et al, 2018; Yang, Heidbüchel, Musolff, Reinstorf, & Fleckenstein, 2018) showed that, even if SAS functions simplify the shapes of the age distributions compared with TTDs, they may not be described well by unimodal distributions. Rodriguez and Klaus (2019) used high frequency (i.e., sub‐daily) stable isotopes in precipitation and discharge over 2 years and found that the SAS function in a slate catchment with complex flow paths may contain several peaks consistent with experimentally identified discharge generation processes.…”
Section: Acknowledging the Multimodality Of Water Age Distributionsmentioning
confidence: 99%
“…This has made the detection of the entire shape of the TTDs more feasible than in the past. High‐frequency tracer observations can now constrain the left‐hand part of TTDs representing the short (e.g., hours to days) and intermediate (e.g., weeks) transport time scales (Rodriguez & Klaus, 2019), while long records of tracers can constrain the right‐hand tail of TTDs associated with long transport time scales (e.g., months to years, Rodriguez, Pfister, Zehe, & Klaus, 2019; Neal et al, 2011). Tracer time series that span several years at high resolution (von Freyberg, Studer, Rinderer, & Kirchner, 2018) will pave the way for the detailed investigation of water flow paths and their influence on TTDs.…”
Section: Acknowledging the Multimodality Of Water Age Distributionsmentioning
confidence: 99%
See 3 more Smart Citations